Nitroglycerin (NTG) Infusion for Intraprocedural Vasospasm in Transarterial Microembolization (TAME): A Case Series - Kuan-Wei Li; Keng-Wei Liang; Wen-Ying Liao; Chien-Kuo Wang; Yi-Sheng Liu; Tai-Hua Yang; Chun-Hsin Wu; Bow Wang (Life)
Transarterial microembolization (TAME) is an innovative approach to treating chronic musculoskeletal pain. During the procedure, intraprocedural vasospasm, presenting juxta-catheter stenosis, and poor distal artery perfusion and flow through the anastomosis commonly pose challenges. Difficulty of the catheter reaching the target vessel and restricted drug delivery are possible consequences. To address these issues, transcatheter nitroglycerin (NTG) infusion at the extremity’s small-sized artery has been introduced. We investigated patients who underwent the TAME procedure wherein NTG was employed and sourced from two institutional settings. Transcatheter NTG infusion was administered in seven instances of chronic musculoskeletal pain manifesting with intraprocedural vasospasm during TAME procedures. Patient profiles, preprocedural imaging, fluoroscopic findings, adverse events, and Numerical Rating Scale (NRS) scores were evaluated. As a result, all seven cases experiencing intraprocedural vasospasm exhibited rapid responses to transcatheter NTG infusion. Angiography conducted pre- and post-infusion demonstrated increased vessel size, resolved proximal catheter stenosis, and improved distal perfusion. One case presented an adverse effect of self-limited transient hypotension. The NRS scores decreased following the procedure. Transcatheter NTG infusion at the extremity’s small-sized muscular artery can be an effective technique for resolving intraprocedural vasospasm in TAME procedures, irrespective of the target diseases and approach vessels.